Newly isolated mutant of Yarrowia lipolytica MK1 as a proper host for efficient erythritol biosynthesis from glycerol. Issue 1 (January 2015) - Mirończuk, Aleksandra M.; Dobrowolski, Adam; Rakicka, Magdalena; Rywińska, Anita; Rymowicz, Waldemar
Highlights Strain Yarrowia lipolytica MK1 is a promising industrial host of erythritol production from glycerol. During RBC the strain Y. lipolytica MK1 was able to produce 224 g l−1 erythritol. UV mutation caused limitation of by-product formation below 2.3%. The Y. lipolytica MK1 biomass contains 80% of unsaturated fatty acids in the total fatty acids pool.